Audit Procedures to Manage Information Systems Based on the DSS02 Domain in the COBIT5 Framework at Double - Six Luxury Hotel Seminyak - Muhammad Sahi; Ida Ayu Gde Suwiprabayanti Putra; I Gusti Ayu Sri Melati (Applied Information System and Management (AISM), 2021)
Double-Six Luxury Hotel is currently implementing Information Technology (IT) to support the company's operations. However, there are obstacles in implementing IT, such as users who fail to log in or log out and there are disruptions to the network server caused by the disconnection of the fiber optic cable. Based on this, it is necessary to audit information system governance. This study using the COBIT 5 Framework with a conceptual method. This research focuses on the DSS (Delivery, Support, and Service) domain in the DSS02 process. The purpose of the study was to determine the current level of capability (as-is) and expected conditions (to-be), gaps, and provide recommendations regarding information system governance at Double-Six Luxury Hotels. The results of this study indicate that the current condition of the DSS02 process capability level is at level 2 (Managed Process) with a percentage of 67.5% in the Very Achieved (L) category where the process has been managed well but only most of it is not entirely and the expected conditions are at level 3 (Build Process). Based on these results, it is known that in the DSS02 process there is a gap of 1 between as-is and to-be, so the management in the DSS02 process is sure to carry out process definition and process development at level 3 (building process) to achieve the specified level target